Adolescent Students’ Perceived Self-efficacy on Disease Prevention Actions and Associated Socio-demographic Factors - Man Kumar Tiruwa; Asmita Koirala; Shanti Prasad Khanal; Suman Kharel; Pradeep Bohora (Contemporary Research: An Interdisciplinary Academic Journal, 2026)
Adolescents are in a critical period of development for forming healthy behaviours; however, empirical data on their self-efficacy in disease prevention are limited in Nepal. The study aims to fill gaps in municipal-level data, specifically regarding self-efficacy and its socio-demographic determinants among adolescents attending schools in grades six to twelve in Bardibas Municipality, Mahottari District. A quantitative cross-sectional design was used. The 280 students studying in four randomly selected community schools selected, using cluster sampling and proportional representation of gender and class. The data were gathered using a self-administered questionnaire that included questions on socio-demographics, precautionary measures, and a 20-item self-efficacy scale with a 5-point Likert scale. The scale had good internal consistency (Cronbach’s alpha = 0.72). SPSS version 20 was used to conduct descriptive statistics, t-tests, ANOVA, and general linear regression analysis. The overall self-efficacy mean score was moderate to high (M = 66.57, SD = 6.95), with the highest scores on nutritional behaviour and hygiene practices and the lowest on mask use. The significant predictors were gender, age, class level, and language (p < 0.05), whereas income, caste, and religion did not have a significant impact. Multivariate analysis revealed that domain-specific behaviours and health practice items were significant predictors of self-efficacy. The overall level of self-efficacy in disease prevention among adolescents was positive; however, there are still some gaps in particular behavioural domains. School- and community-based health education programs that are culturally are gender-sensitive to support self-efficacy and preventive actions in adolescents are urgently needed.